2021
DOI: 10.2196/25602
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Readability of Web-Based Information for Patients With Pancreatic Cysts: DISCERN and Readability Test Analysis

Abstract: Background Pancreatic cysts are a complex medical problem with several treatment options. Patients use web-based health information to understand their conditions and to guide treatment choices. Objective The goal of this study was to describe the quality and readability of publicly available web-based information on pancreatic cysts and to compare this information across website affiliations. Methods A Goog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…Previous studies on nonrehabilitation conditions have reported below-average resource quality, specifically, the management of many orthopedic and vascular conditions. 18,21,27 In contrast, patient resources for upper limb spasticity are of good quality, which is consistent with studies that have evaluated pelvic floor exercises and total hip and knee replacements. 25,27 This could be attributed to the fact that pelvic floor issues and joint replacements are common in the United States.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Previous studies on nonrehabilitation conditions have reported below-average resource quality, specifically, the management of many orthopedic and vascular conditions. 18,21,27 In contrast, patient resources for upper limb spasticity are of good quality, which is consistent with studies that have evaluated pelvic floor exercises and total hip and knee replacements. 25,27 This could be attributed to the fact that pelvic floor issues and joint replacements are common in the United States.…”
Section: Discussionsupporting
confidence: 74%
“…Of the Websites, 63.9% and 63.6% of YouTube videos failed to mention any risk factors for treatments receiving a DISCERN score of 1. Although this was not commonly observed in similar studies, Oman et al 21 reported similar shortcomings, reporting that the description of the risk associated with treatment was suboptimal. A potential solution is to incorporate hyperlinks, which allow patients to obtain further information if needed.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Section three (question 16) helps determine the overall rating of the publication on a scale of 1-5 after rating the previous 15 questions. 12 Using the same list of 100 most popular search results for the common GAS-related search terms as described above, the quality of these online sources was determined using the DISERN score. Two researchers (A. Z.F and A.…”
Section: Quality Of Web-based Informationmentioning
confidence: 99%
“…Although there are several methods to assess the quality of texts, a common and well-validated method that has previously been used to evaluate online sources is the DISCERN tool. [12][13][14] The transgender population faces unique barriers to health literacy. Studies indicate that 24% of transgender patients have only completed elementary level education, and 60% have only secondary education.…”
Section: Introductionmentioning
confidence: 99%